Dialog interkulturowy na lekcji języka angielskiego w kontekście polskim - Sobkowiak, Paweł (Neofilolog, 2019)
This article attempts to persuade the reader that in order to prepare our learners for using foreign languages (FL) efficiently in the global, multicultural world, FL pedagogy needs to reconsider its long-established goals of teaching and adopt a more openended, intercultural (IC), processoriented approach. Thus, the objective of language training, apart from the traditional work on the four skills, should be raising awareness of difference and diversity between representatives of various cultures and engaging learners in the process of decentering, acquiring desirable attitudes to otherness, fostering empathy, developing their ability to mediate, promoting tolerance, and benefiting rather than suffering from IC experience. The dialogic approach, which will be discussed in the paper, seems to be tailormade to achieve this. In the empirical part of the article, the author reports the results of qualitative research which involved observations of English lessons in several high schools in Poznań, Poland. The study aimed at answering the questions whether and to what degree a homogeneous FL classroom in Poland is conducive to developing IC sensitivity and competence. The results demonstrate that IC dialogue plays a marginal role and teachers do not engage learners in discussion, analysis or reflection about the interrelationships between language, identity, culture and communication. If culture appears in the classroom, it is taught in a very traditional way, namely it is limited mostly to transferring declarative knowledge about various aspects of foreign culture/s.